Same-day transfer for the invasive strategy of patients with non-ST-segment elevation acute coronary syndrome admitted to spoke hospitals: Data from the Emilia-Romagna Regional Network. Issue 6 (October 2016) - Campo, Gianluca; Menozzi, Mila; Guastaroba, Paolo; Vignali, Luigi; Belotti, Laura MB; Casella, Gianni; Berti, Elena; Solinas, Emilia; Guiducci, Vincenzo; Biscaglia, Simone; Pavasini, Rita; De Palma, Rossana; et al.
Background: The service strategy (same-day transfer between spoke hospital and hub centre with catheterisation laboratory (cath-lab) facility to perform invasive procedures) has been suggested to improve the management of patients with non-ST-segment elevation acute coronary syndrome (NSTEACS) admitted to spoke hospitals. We used data from a large prospective Italian registry to describe application, performance and outcome of the service strategy in the daily clinical practice. Methods: This study was based on an observational, post-hoc analysis of all consecutive NSTEACS patients admitted to spoke non-invasive hospitals of the Emilia-Romagna regional network and receiving coronary artery angiography (CAA)±percutaneous coronary intervention (PCI). We evaluated: application of service strategy, time to cath-lab access, hospital stay length, 30-days occurrence of adverse events. Results: From January 2011–December 2012, 2952 NSTEACS consecutive patients were admitted to spoke non-invasive hospitals and received CAA. Overall, 1765 (60%) patients were managed with a service strategy. After multivariable analysis, service strategy emerged as independent predictor of faster access to cath-lab (within 72 h: hazard ratio (HR) 2.3, 95% confidence interval (CI) 1.9–2.7, p <0.0001; within 24 h: HR 2.8, 95% CI 2.2–3.3, p <0.0001, respectively). Service strategy significantly reduced hospital stay length (–5.5 days, p <0.0001). We estimated a mean of €1590 saved for each patient managed with service strategy. Thirty-day occurrence of adverse events did not differ between patients managed with or without a service strategy. Conclusions: In our daily clinical practice, a service strategy seems to be an effective approach to optimise the invasive management of NSTEACS patients admitted to spoke hospitals.